THE INFLUENCE OF PRODUCT KNOWLEDGE ON GREEN PURCHASE INTENTION, THE ROLE OF ATTITUDE AS MEDIATING VARIABLE - Manopo, Andi; Tumbuan, Willem J. F. A.; Gunawan, Emilia M. (Universitas Sam Ratulangi, 2021)
Environmental issues have occurred since the industrial era and are finally realized by many companies and consumers because the impact is very detrimental to all creatures on earth nowadays. Afterwards, companies started to make environmental friendly products because of moral responsibilities and demands from the regulators in many countries. In the marketing context, companies also implemented green marketing to stimulate factors that can support consumer's green purchase intention. This study aims to analyze the influence of product knowledge and attitudes toward green products on the green purchase intention directly and indirectly. The sampling used in this study was 120 qualified respondents employing a purposive sampling technique. The analysis tool utilized in this study was PLS-SEM using SmartPLS version 3.2.9. Based on the analysis, product knowledge and attitudes toward green products had a significant influence on green purchase intention directly and indirectly.Â Keywords: product knowledge, attitude, green purchase intention